Interactions of PRP2 protein with pre-mRNA splicing complexes in Saccharomyces cerevisiae. - King, D S (1990)
PRP2 protein of Saccharomyces cerevisiae is required for the pre-mRNA splicing reaction but not for the early stages of spliceosome assembly. Using anti-PRP2 antibodies we demonstrate that PRP2 protein is associated with spliceosomes prior to, and throughout step 1 of the splicing reaction. Heat-inactivated prp2 protein, by contrast, does not seem to associate with spliceosomes. By elution of electrophoretically distinct spliceosomal complexes from non-denaturing gels we identify the specific complex with which PRP2 initially interacts in the pathway of spliceosome assembly.